Market transparency and consumer search - Evidence from the German retail gasoline market - Simon Martin (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We study a novel trade-off in market transparency regulation by estimating a structural model of the German retail gasoline market. Transparent environments enable easy price comparisons and match findings. Restricting transparency such that only the cheapest offers are shown induces firms to compete for attention, but matching is inefficient. We find that there is an inverse u-shaped relationship between consumer welfare and market transparency. Consumer welfare is maximal when only the first 20% of prices are shown, which decreases consumer expenditures by 1.2%. Our framework allows estimating games of incomplete information with very lax data requirement.
Keywords: D22; D43; D83; L13; L50; 330; market transparency; consumer search; awareness; consideration sets; retail gasoline prices